Hyperamylasemia and pancreatitis following spiral enteroscopy - Christopher W Teshima; Huseyin Aktas; Ernst J Kuipers; Peter B Mensink (Canadian Journal of Gastroenterology)
BACKGROUND: Acute pancreatitis is a significant potential complication with double-balloon enteroscopy. Hyperamylasemia is frequently observed after both double-balloon enteroscopy and single-balloon enteroscopy but often without associated pancreatitis. Whether the same phenomenon occurs with spiral enteroscopy is currently unknown.